Downregulation of MicroRNA 29a/b exacerbated diabetic retinopathy by impairing the function of Müller cells via Forkhead box protein O4. (May 2018) - Zhang, Jiayu; Wu, Liang; Chen, Jiawei; Lin, Sisi; Cai, Daqiu; Chen, Chengwei; Chen, Zhenguo
Background: Diabetic retinopathy is a neurological disease, which can lead to blindness in severe cases. The pathogenesis underlying diabetic retinopathy is unclear. The aim of this study was to explore the role of dysregulated microRNA 29a/b in the onset and progression of diabetic retinopathy. Methods: Diabetes mellitus was induced in rats using 60 mg/kg of streptozotocin. Glucose (5.5 and 25 mM) was used to stimulate rat retinal Müller cells. Real-time polymerase chain reaction and Western blot analyses were used to determine gene expression. A luciferase reporter assay was conducted to validate the relationship of microRNA 29a/b with glioma-associated oncogene homolog 1 and Forkhead box protein O4. Results: The expression of microRNA 29a/b and glutamine synthetase decreased in both diabetes mellitus rats and rat retinal Müller cells stimulated with high glucose, whereas the expression of sonic hedgehog, glioma-associated oncogene homolog 1, glial fibrillary acidic protein, and vascular endothelial growth factor, as well as the content of glutamate, increased. Dysregulated microRNA 29a/b was directly regulated by the sonic hedgehog–glioma-associated oncogene homolog 1 signalling pathway, and microRNA 29a and microRNA 29b targeted Forkhead box protein O4 and regulated its expression. Conclusion: Downregulation of microRNA 29a/b, mediated by the sonic hedgehog–glioma-associated oncogene homolog 1 signalling pathway, exacerbated diabetic retinopathy by upregulating Forkhead box protein O4.